2013
DOI: 10.1186/1471-2458-13-181
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of knowledge of sex partner serostatus among high-risk Peruvian men who have sex with men and transgender women: implications for HIV prevention

Abstract: BackgroundKnowledge of a sex partner’s HIV serostatus can influence sexual behavior and inform harm-reduction strategies. We sought to determine how often Peruvian men who have sex with men (MSM) and transgender women (TW) knew the HIV serostatus of their sex partners, if this knowledge was associated with any predictive factors or unprotected anal intercourse (UAI), and if UAI was associated with partner serostatus.MethodsWe analyzed data from the 2008 Peruvian MSM Sentinel Surveillance Survey. Data were coll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
31
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 17 publications
(14 reference statements)
7
31
1
Order By: Relevance
“…More than 50% of the kathoey sex workers interviewed by Nemoto and colleagues in Bangkok had never been tested [18]. Also, data suggest that few transgender women know the HIV status of their sexual partners [29]. Lack of inclusion in HIV awareness and prevention campaigns as well as competing priorities in the lives of transgender women may contribute to low rates of HIV testing [30, 31].…”
Section: Continuum Of Hiv Care and Treatmentmentioning
confidence: 99%
“…More than 50% of the kathoey sex workers interviewed by Nemoto and colleagues in Bangkok had never been tested [18]. Also, data suggest that few transgender women know the HIV status of their sexual partners [29]. Lack of inclusion in HIV awareness and prevention campaigns as well as competing priorities in the lives of transgender women may contribute to low rates of HIV testing [30, 31].…”
Section: Continuum Of Hiv Care and Treatmentmentioning
confidence: 99%
“…The negative association of two or more sexual partners and partner's concurrency with serostatus knowledge has been shown in other populations [1, 3, 7], and suggests that women with the riskiest behaviors are least likely to know of their infection risk. This may reflect fewer opportunities or expectations to discuss personal matters such as serostatus with increasing numbers of partners, particularly among those who are less well known [11, 23]. Prior research has suggested as well that intimacy, trust, and shared responsibility are often present among main and longer-term partners, and can reduce serostatus communication barriers due to fear or embarrassment [11, 24].…”
Section: Discussionmentioning
confidence: 99%
“…This may reflect fewer opportunities or expectations to discuss personal matters such as serostatus with increasing numbers of partners, particularly among those who are less well known [11, 23]. Prior research has suggested as well that intimacy, trust, and shared responsibility are often present among main and longer-term partners, and can reduce serostatus communication barriers due to fear or embarrassment [11, 24]. This may explain why women who were living with their most recent male sex partner were more likely to be aware of his HIV status, given the potential greater intimacy and stability of cohabitation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations